The pharmacological interactions between direct-acting antivirals for the treatment of chronic hepatitis c and psychotropic drugs. Issue 10 (3rd October 2018) - Roncero, Carlos; Villegas, Jose Luis; Martínez-Rebollar, Maria; Buti, Maria
ABSTRACT: Introduction : Most direct-acting antivirals (DAAs) and psychotropic drugs are metabolized by or induct/inhibit CYP enzymes and drug transporters. Although they are frequently coadministered, the drug–drug interactions (DDIs) have been little studied. Therefore, the aim of this review is to describe the interactions between the approved DAA or combination regimens and the main psychoactive substances, including legal and illegal drugs of abuse. Areas covered : We performed a literature search on PubMed database on drug interactions with the currently available antivirals for hepatitis C and a review of the information on pharmacokinetics, metabolism, and drug interactions from www.hep-druginteractions.org and from all the Summary of Product Characteristics (SmPC). This review covers the DDI between the DAA regimens approved, such as simeprevir and sofosbuvir, paritaprevir, glecaprevir, voxilaprevir, ombitasvir, ledipasvir, daclatasvir and sofosbuvir, elbasvir and grazoprevir, sofosbuvir and velpatasvir, glecaprevir/pibrentasvir, sofosbuvir and velpatasvir, and main psychotropic agents. Expert Commentary : DAA regimens based on sofosbuvir combination usually have less DDI than protease inhibitor-based regimens. Among protease inhibitors regimens, new combinations, such as glecaprevir/elbasvir and grazoprevir/elbasvir, seemed to have less DDI than the combination POrD (paritaprevir/ombitasvir/ritonavir/dasabuvir). However, the analysis of each interaction is theoretical and further interaction studies would be necessary to confirm actual effect.